Reconstruction of The Application of Restorative Justice to Criminal Offenses Due to Negligence (Culpa) in The Indonesian Criminal Justice System - Muhammad Ali; Mispansyah Mispansyah; Diana Haiti (Law and Justice research journal, 2025)
The paradigm of the Indonesian criminal justice system is currently undergoing a significant shift from a retributive approach toward a restorative one. Criminal offenses resulting from negligence (culpa) present a unique case within this transition, as they lack malicious intent (mens rea in the form of dolus), yet often result in severe harm or loss of life. Despite its potential, the application of restorative justice for culpa offenses remains hindered by fragmented and sectoral regulations among law enforcement agencies, leading to legal uncertainty and inconsistent implementation. This research aims to analyze the urgency of restorative justice in negligence cases and proposes a model for its reconstruction. Using a normative juridical research method with statutory and conceptual approaches, this study examines existing regulations from the National Police, the Attorney General’s Office, and the Supreme Court. The findings indicate that the current framework requires a structural reconstruction through the synchronization of inter-institutional policies and the integration of restorative justice principles into the National Criminal Procedure Code (KUHAP). This reconstruction is essential to ensure a unified standard that balances legal certainty, the rehabilitation of the offender, and the restoration of the victim’s rights in unintentional crimes.